PERANCANGAN KIOS IPTEK DALAM MANAJEMEN PERTANIAN BAGI PETANI - Asmy, Yumma Yustika; Kamila, Rizqia Awalu; Hasugian, Leonardi Paris (JURISMA : Jurnal Riset Bisnis & Manajemen, 2022)
The purpose of this study is to analyze problems with the capacity and capability of the availability of new innovations found in the use of information and communication technology. This research is an analysis in examining agricultural management in the IpTek Kiosk media based on Agricultural Information and Communication Technology Change. The method of this research was conducted using qualitative descriptive writing methods by collecting data through literature studies and using the Model Analysis PEST and SWOT. The results of this study are to obtain an analysis of the study of agricultural management in the IpTek Kiosk media based on changes in agricultural Information and Communication Technology and the extent to which the IpTek Kiosk media is ideal or not in ensuring the design and development of agricultural management later. It is expected that the impact of the agricultural management analysis study can help farmers both in terms of commodities and the farming market by facilitating farmers in implementing information and communication technology. Therefore farmers can more actively seek new information independently and reduce the cosmopolitan numbers of farmers in Indonesia. so that later it can improve the management of agricultural segmentation in achieving Indonesian Food Security.